'You actually see what occupational therapists do in real life': Outcomes and critical features of first-year practice education placements. (October 2020) - Honey, Anne; Penman, Merrolee
Introduction: First-year practice education placements have numerous benefits for occupational therapy students but are resource intensive. In considering alternatives, it is critical to consider students' voices to ensure that planned experiences enable students to achieve the outcomes they value and need. This study examined undergraduate occupational therapy students' views about important outcomes and characteristics of first-year placements. Methods: Focus groups were conducted with 18 occupational therapy students and analysed using constant comparative analysis. Findings: Two overarching outcomes were valued: confirmation of occupational therapy as a career choice and experience to draw on for future learning and practice. These outcomes were achievable through four proximal outcomes: understanding occupational therapy; understanding clients; finding out about myself and developing skills. The extent to which the valued outcomes were attained was determined by eight critical experiences: observing an occupational therapist in action; seeing real clients with real issues; seeing positive impact; seeing the bigger picture; accessing the occupational therapist's reasoning; hands-on doing; getting feedback on skills and thinking analytically/reflectively. Conclusion: In designing first-year placements, practice educators and academics need to ensure that students are provided with experiences that incorporate reality, participation and making connections to a bigger picture of occupational therapy service provision.